Processing method of cerium-doped gadolinium aluminum gallium garnet wafer

Through laser hole drilling and post-annealing treatment, the problem of Ce:GAGG crystals prone to cracking in traditional mechanical processing is solved, the processing yield and finish are improved, and efficient wafer processing is achieved.

CN119710939APending Publication Date: 2025-03-28BEIJING SINOMA SYNTHETIC CRYSTALS CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411949638.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Due to its high brittleness, traditional mechanical processing methods are difficult to obtain complete and high-quality wafers, and the processing yield is low.

Method used

Laser drilling is used instead of traditional mechanical drilling, and combined with post-annealing treatment, including the steps of heating to 1100℃~1400℃, insulation for 12h~48h, cooling to room temperature, and finally polishing.

Benefits of technology

It effectively reduces wafer cracking caused by mechanical processing stress, improves the processing yield of Ce:GAGG wafers to more than 70%, and obtains wafers with high surface finish.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005214551190000061
    Figure BDA0005214551190000061
  • Figure BDA0005214551190000071
    Figure BDA0005214551190000071
Patent Text Reader

Abstract

The invention provides a processing method of a cerium-doped gadolinium aluminum gallium garnet wafer. The processing method comprises the following steps: (1) wafer cutting: cutting a crystal into wafers; (2) laser drilling, wherein laser is used for drilling on the wafer; wherein the punching speed ranges from 5 mm / s to 100 mm / s; (3) annealing post-treatment: carrying out annealing treatment on the punched wafer under the conditions that the temperature is increased to 1100-1400 DEG C at the temperature increasing rate of 10-40 DEG C / h, heat preservation is carried out for 12-48 hours, and then the temperature is reduced to the room temperature at the temperature reducing rate of 5-30 DEG C / h; and (4) optical processing: polishing the annealed wafer. When the method is used for processing the cerium-doped gadolinium aluminum gallium garnet wafer, the processing yield of the wafer can be improved, and the processing yield of the wafer can reach 70% or above.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of inorganic non-metallic material processing, and in particular to a processing method of a cerium-doped gadolinium aluminum gallium garnet wafer. Background Art

[0002] Cerium-gadolinium-doped aluminum gallium garnet (Ce:GAGG) scintillator crystal has the advantages of high light yield (the highest among currently known oxide scintillator crystals), high energy resolution, fast decay time, no self-radiation and no deliquesce. It is a new type of rare earth oxide scintillator crystal with excellent performance. It has a broad application market in high-energy particle detection, nuclear medicine imaging, security inspection and industrial non-destructive detection, especially in the field of single photon emission computed tomography (SPECT) imaging.

[0003] However, since Ce:GAGG crystals are hard and brittle, there are still some problems in the processing of ultra-thin wafers. Traditional wafer drilling generally adopts mechanical processing methods. According to the requirements of the hole size, a suitable drill bit is selected, and then the workpiece is clamped in a vise, the position of the workpiece is adjusted to ensure that the drill bit coincides with the drilling position, and a suitable drilling speed is selected for drilling. Due to the high brittleness of Ce:GAGG crystals, the clamping of the vise and the impact of the drill bit during the drilling process are particularly prone to cause wafer cracking, and the yield rate is low. Moreover, the stress generated during mechanical processing such as cutting and drilling is easy to extend to the later optical processing process, thereby causing wafer cracking. It is difficult to obtain complete and smooth Ce:GAGG wafers using traditional wafer processing methods, and the processing yield rate is low, usually only about 40%. Summary of the invention

[0004] The purpose of this application is to provide a method for processing a Ce-doped Gadolinium-doped Aluminum Gallium Garnet wafer to reduce wafer cracking caused by mechanical processing stress and improve the processing yield of Ce:GAGG wafers. The specific technical solution is as follows:

[0005] The present application provides a method for processing a cerium-doped gadolinium aluminum gallium garnet wafer, which comprises the following steps:

[0006] (1) Wafer cutting: cutting the crystal into wafers;

[0007] (2) Laser drilling: drilling holes on the wafer using a laser; wherein the drilling speed is 5 mm / s to 100 mm / s;

[0008] (3) Post-annealing treatment: The wafer after drilling is subjected to annealing treatment, wherein the annealing treatment conditions are: heating to 1100°C to 1400°C at a heating rate of 10°C / h to 40°C / h, keeping the temperature for 12h to 48h, and then cooling to room temperature at a cooling rate of 5°C / h to 30°C / h;

[0009] (4) Optical processing: polishing the wafer after annealing.

[0010] In one embodiment of the present application, in step (3), the annealing treatment conditions are: heating to 1200°C to 1400°C at a heating rate of 15°C / h to 30°C / h, keeping warm for 24h to 48h, and then cooling to room temperature at a cooling rate of 10°C / h to 20°C / h.

[0011] In some embodiments of the present application, the diameter of the hole obtained after punching the wafer in step (2) is 0.5 mm to 10 mm, and the error of the diameter of the hole is less than or equal to 0.05 mm.

[0012] In some embodiments of the present application, in step (1), the cutting speed is 0.1 mm / min to 1 mm / min, and the thickness of the wafer is 0.2 mm to 1 mm.

[0013] In some embodiments of the present application, in step (4), the polishing step includes: coarse grinding, fine grinding, and chemical mechanical polishing.

[0014] In some embodiments of the present application, the coarse grinding includes: using W40~W28 corundum for coarse grinding; the fine grinding includes: using W10~W7 corundum powder for fine grinding; the chemical mechanical polishing includes: grinding and polishing with polishing liquid, and the grinding and polishing rotation speed is 5rpm~50rpm and the pressure is 2kPa~20kPa.

[0015] In some embodiments of the present application, the polishing liquid includes CeO2, diamond micropowder, H3PO4, and deionized water, and the particle size of the diamond micropowder is 0.5μm to 5μm; based on the mass of the polishing liquid, the mass percentage of CeO2 is 1% to 10%, the mass percentage of the diamond micropowder is 10% to 20%, the mass percentage of H3PO4 is 1% to 5%, and the mass percentage of deionized water is 65% to 88%.

[0016] In some embodiments of the present application, the processing yield of the wafer is greater than or equal to 70%.

[0017] Beneficial effects of this application:

[0018] The present application provides a method for processing a cerium-doped gadolinium aluminum gallium garnet wafer. By processing ultra-thin Ce:GAGG crystals by laser drilling combined with annealing post-treatment, it is possible to effectively avoid wafer cracking caused by mechanical stress caused by cutting, traditional mechanical drilling, etc., thereby obtaining a complete wafer, which provides conditions for subsequent chemical mechanical polishing of the wafer. In addition, the use of laser drilling can reduce the hole opening error. By using the wafer processing method provided by the present application, a complete wafer with a high surface finish can be obtained, and the wafer processing yield rate can reach more than 70%. DETAILED DESCRIPTION

[0019] The following will be combined with the embodiments of the present application to clearly and completely describe the technical solutions in the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. All other embodiments obtained by those skilled in the art based on the present application belong to the scope of protection of the present application.

[0020] Ce:GAGG crystals have a broad application market in high-energy particle detection, nuclear medical imaging, security inspection, and industrial non-destructive detection, but Ce:GAGG crystals are very brittle, and it is difficult to obtain complete, smooth wafers using traditional processing methods, and the wafer processing yield is low. Based on this, the present application provides a wafer processing method to improve the processing yield of Ce:GAGG wafers, especially the processing yield of ultra-thin Ce:GAGG wafers.

[0021] The present application provides a method for processing a cerium-doped gadolinium aluminum gallium garnet wafer, which comprises the following steps:

[0022] (1) Wafer cutting: cutting the crystal into wafers;

[0023] (2) Laser drilling: drilling holes on the wafer using a laser; wherein the drilling speed is 5 mm / s to 100 mm / s;

[0024] (3) Post-annealing treatment: The punched wafer is annealed. The annealing conditions are as follows: heating to 1100°C to 1400°C at a heating rate of 10°C / h to 40°C / h, keeping the temperature for 12h to 48h, and then cooling to room temperature at a cooling rate of 5°C / h to 30°C / h.

[0025] (4) Optical processing: Polishing the wafer after annealing.

[0026] In the wafer processing process, step (2) uses laser drilling instead of traditional mechanical drilling, and controls the speed of laser drilling. For example, the drilling speed can be 5mm / s, 16mm / s, 28mm / s, 40mm / s, 50mm / s, 65mm / s, 77mm / s, 89mm / s, 100mm / s or a range consisting of any two of these values, thereby avoiding the influence of mechanical vibration on the wafer, and the wafer is not easy to crack. If the drilling speed is less than 5mm / s, the hole will be blocked during the drilling process, the drilling will fail, and the wafer processing yield will be low; if the drilling speed is greater than 100mm / s, the wafer will quickly absorb the laser energy and then cool down quickly, which is easy to generate thermal stress and the wafer processing yield will be low. By adjusting the laser drilling speed within the above range, not only the aperture accuracy can be improved, but also the damage to the wafer can be reduced, thereby improving the processing yield of Ce:GAGG wafers.

[0027] Step (3) annealing the punched wafer, and controlling the annealing conditions. For example, the heating rate can be 10°C / h, 18°C / h, 25°C / h, 30°C / h, 35°C / h, 40°C / h, or a range consisting of any two of the values ​​therein; the annealing temperature can be 1100°C, 1160°C, 1200°C, 1250°C, 1300°C, 1340°C, 1400°C, or a range consisting of any two of the values ​​therein; the holding time can be 12h, 16h, 20h, 24h, 30h, 36h, 40h, 43h, 48h, or a range consisting of any two of the values ​​therein; and the cooling rate can be 5°C / h, 10°C / h, 15°C / h, 20°C / h, 24°C / h, 30°C / h, or a range consisting of any two of the values ​​therein. When the heating rate is greater than 40℃ / h or the cooling rate is greater than 30℃ / h, the temperature difference between the surface and the inside of the chip will quickly appear, generating thermal stress, causing deformation or even cracking of the chip, seriously affecting the integrity and subsequent processing performance of the chip; when the heating rate is less than 10℃ / h or the cooling rate is less than 5℃ / h, the production cycle is extended and the production cost is increased. When the annealing temperature is greater than 1400℃ or the holding time is greater than 48h, the chip lattice may be distorted and the chip defects may increase. When the annealing temperature is less than 1100℃ or the holding time is less than 12h, the mechanical stress inside the chip is not fully eliminated, affecting the processing yield of the chip. Therefore, by regulating the heating rate, cooling rate, annealing temperature and holding time of the post-annealing treatment within the scope of this application, the mechanical stress of the Ce:GAGG chip can be effectively eliminated and the processing yield of the Ce:GAGG chip can be improved.

[0028] In summary, the use of laser drilling combined with annealing post-processing can reduce chip cracking caused by mechanical processing stress, provide conditions for subsequent chemical mechanical polishing of the chip, and obtain complete chips with high surface finish. The chip processing yield can reach more than 70%.

[0029] In some embodiments of the present application, in step (3), the annealing conditions are: heating to 1200°C to 1400°C at a heating rate of 15°C / h to 30°C / h, keeping warm for 24h to 48h, and then cooling to room temperature at a cooling rate of 10°C / h to 20°C / h. For example, the heating rate can be 15°C / h, 18°C / h, 25°C / h, 30°C / h, or a range consisting of any two of the values, the annealing temperature can be 1200°C, 1250°C, 1300°C, 1340°C, 1400°C, or a range consisting of any two of the values, the holding time can be 24h, 30h, 36h, 40h, 43h, 48h, or a range consisting of any two of the values, and the cooling rate can be 10°C / h, 13°C / h, 15°C / h, 20°C / h, or a range consisting of any two of the values. Controlling the annealing conditions within the above range can eliminate the mechanical stress introduced by the wafer due to cutting, etc., reduce wafer cracking, and improve the processing yield of the wafer.

[0030] In some embodiments of the present application, the diameter of the hole obtained after the wafer is punched in step (2) is 0.5mm to 10mm, and the error of the diameter of the hole is less than or equal to 0.05mm. For example, the diameter of the hole can be 0.5mm, 1.6mm, 2.8mm, 4.3mm, 6mm, 7mm, 8.5mm, 9.4mm, 10mm or a range consisting of any two of the numerical values, and the error of the diameter of the hole can be 0.01mm, 0.02mm, 0.03mm, 0.04mm, 0.05mm or a range consisting of any two of the numerical values. The diameter of the hole is within the above range, which can match different application scenarios. The error of the punching is within the above range, indicating that the error of laser punching is small, the aperture size can be accurately controlled, the aperture error can be reduced, and high-precision punching can be achieved, thereby improving the processing yield of Ce:GAGG wafers.

[0031] In some embodiments of the present application, in step (1), the cutting speed is 0.1 mm / min to 1 mm / min, and the thickness of the wafer is 0.2 mm to 1 mm. For example, the cutting speed can be 0.1 mm / min, 0.3 mm / min, 0.4 mm / min, 0.6 mm / min, 0.8 mm / min, 1 mm / min, or a range consisting of any two of the values, and the thickness of the wafer can be 0.2 mm, 0.3 mm, 0.5 mm, 0.6 mm, 0.8 mm, 1 mm, or a range consisting of any two of the values. By controlling the cutting speed and the thickness of the wafer within the above range, a complete and uniformly thick ultra-thin Ce:GAGG wafer can be obtained, thereby improving the processing yield of the wafer.

[0032] In some embodiments of the present application, in step (4), the step of optical processing, i.e., the step of polishing, includes: coarse grinding, fine grinding, and chemical mechanical polishing. In some embodiments of the present application, coarse grinding includes: using corundum of W40 to W28 for coarse grinding; fine grinding includes: using corundum powder of W10 to W7 for fine grinding; chemical mechanical polishing includes: grinding and polishing with polishing liquid, the rotation speed of grinding and polishing is 5rpm to 50rpm, and the pressure is 2kPa to 20kPa. For example, the rotation speed of grinding and polishing can be 5rpm, 15rpm, 30rpm, 40rpm, 50rpm, or a range consisting of any two of the values; the pressure of grinding and polishing can be 2kPa, 5kPa, 8kPa, 12kPa, 16kPa, 20kPa, or a range consisting of any two of the values. In some embodiments of the present application, the polishing liquid includes CeO2, diamond micropowder, H3PO4, and deionized water, and the particle size of the diamond micropowder is 0.5μm to 5μm; based on the mass of the polishing liquid, the mass percentage of CeO2 is 1% to 10%, the mass percentage of diamond micropowder is 10% to 20%, the mass percentage of H3PO4 is 1% to 5%, and the mass percentage of deionized water is 65% to 88%. For example, the particle size of diamond powder can be 0.5μm, 1μm, 2μm, 3μm, 4μm, 5μm or a range consisting of any two of them; the mass percentage of CeO2 can be 1%, 3%, 5%, 6%, 8%, 10% or a range consisting of any two of them; the mass percentage of diamond powder can be 10%, 13%, 16%, 20% or a range consisting of any two of them; the mass percentage of H3PO4 can be 1%, 3%, 5% or a range consisting of any two of them; the mass percentage of deionized water can be 65%, 69%, 75%, 80%, 88% or a range consisting of any two of them. The annealed wafer is first subjected to the above-mentioned rough grinding and fine grinding, and then chemically mechanical polishing is performed using the above-mentioned polishing liquid, and the speed and pressure of the chemical mechanical polishing are controlled within the above-mentioned range, so that a wafer with high surface finish can be obtained.

[0033] In some embodiments of the present application, the processing yield of the wafer is greater than or equal to 70%.

[0034] The present application has no particular restrictions on the equipment for crystal cutting, as long as the purpose of the present application can be achieved. For example, a diamond wire saw can be used for cutting. The present application has no particular restrictions on the equipment for laser drilling, as long as the purpose of the present application can be achieved. For example, a laser cutting machine can be used. The present application has no particular restrictions on the equipment for post-annealing treatment, as long as the purpose of the present application can be achieved. For example, an annealing furnace can be used.

[0035] Example

[0036] Hereinafter, examples and comparative examples are given to more specifically illustrate the embodiments of the present application. Various tests and evaluations are carried out according to the following methods. In addition, unless otherwise specified, "parts" and "%" are based on mass.

[0037] Test methods and equipment:

[0038] Hole diameter test:

[0039] The hole diameter of the wafer after punching is measured using an image analyzer. Each hole diameter is tested three times, and the average value of the three tests is taken as the hole diameter of the wafer.

[0040] Error of hole diameter:

[0041] Error of hole diameter = actually measured hole diameter - designed hole diameter.

[0042] Processing yield of wafer:

[0043] Processing yield of wafer = (number of intact wafers after optical processing / number of wafers obtained by cutting) × 100%.

[0044] Example 1

[0045] <Ce:GAGG Wafer Processing>

[0046] The crystal to be processed is cut into wafers with a thickness of 0.5 mm at a speed of 0.5 mm / min using a diamond wire cutting machine. A laser cutting machine is used to punch holes in the above wafers at a speed of 50 mm / s, and the diameter of the holes is 5 mm. The above wafers after punching are heated to 1200 °C at a heating rate of 25 °C / h, held for 36 h, and then cooled to room temperature at a cooling rate of 20 °C / h for annealing treatment. The wafers after the above annealing treatment are polished. First, they are coarsely ground with W30 carborundum, then finely ground with W8 corundum powder, and finally, chemical mechanical polishing is carried out using a polishing solution. The rotation speed of chemical mechanical polishing is 30 rpm, the pressure is 10 kPa, and the polishing solution includes 5% by mass of CeO2, 15% by mass of diamond micropowder with a particle size of 2 μm, 3% by mass of H3PO4, and 77% by mass of deionized water.

[0047] Examples 2 to 19

[0048] Except for adjusting the relevant parameters according to Table 1, the rest are the same as in Example 1.

[0049] Comparative Example 1

[0050] <Ce:GAGG Wafer Processing>

[0051] Use a diamond wire cutting machine to cut the crystal to be processed into wafers with a thickness of 0.5 mm at a speed of 0.5 mm / min. Use a laser cutting machine to drill holes in the above wafers at a speed of 50 mm / s, and the diameter of the holes is 5 mm. Polish the wafers after the above laser drilling, and the polishing steps are the same as those in Example 1.

[0052] Comparative Example 2

[0053] <Ce:GAGG Wafer Processing>

[0054] Use a diamond wire cutting machine to cut the crystal to be processed into wafers with a thickness of 0.5 mm at a speed of 0.5 mm / min. Clamp the above wafers in a bench vise, adjust the position of the wafers to ensure that the drill bit coincides with the drilling position, the diameter of the drill bit is 5 mm, and perform mechanical drilling at a drilling speed of 0.4 mm / min. Perform post-annealing treatment and polishing on the wafers after the above mechanical drilling, and the post-annealing treatment and polishing steps are the same as those in Example 1.

[0055] Comparative Examples 3 to 9

[0056] Except for adjusting the relevant parameters according to Table 1, the rest are the same as in Example 1.

[0057] Table 1

[0058]

[0059]

[0060] Note: " / " in Table 1 indicates no relevant parameters.

[0061] It can be seen from Examples 1 to 19 and Comparative Examples 1 and 2 that by processing Ce:GAGG wafers in a combination of laser drilling and post-annealing treatment, the processing yield of the wafers can be improved, and the processing yield of the wafers can reach more than 70%. Only by processing Ce:GAGG wafers by replacing traditional mechanical drilling with laser drilling, the wafer yield is only 48%. By processing Ce:GAGG wafers in a combination of mechanical drilling and post-annealing treatment, the wafer yield is 42%. Thus, it shows that the wafer processing method provided by the present application can improve the processing yield of Ce:GAGG wafers.

[0062] It can be seen from Examples 1 to 15 and Comparative Examples 3 to 8 that controlling the conditions of the post-annealing treatment within the scope of the present application can improve the processing yield of the wafers. Using annealing conditions outside the scope of the present application for post-annealing treatment, the processing yield of the wafers is low, only about 55%.

[0063] It can be seen from Example 16, Example 17 and Comparative Example 9 that the processing yield rate of the wafer can be improved by controlling the laser drilling speed within the range of the present application. When the drilling speed is greater than 100 mm / s, the wafer quickly absorbs the laser energy and then cools down quickly, which easily generates thermal stress and the wafer processing yield rate is low, only 60%.

[0064] The processing yield rate of Example 2 is 85%, which shows a high processing yield rate, but due to the low heating rate, the production cycle will be extended and the production cost will increase; the processing yield rate of Example 8 is 85%, which shows a high processing yield rate, but due to the low cooling rate, the production cycle will be extended and the production cost will increase.

[0065] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the scope of protection of the present application.

Claims

1. A method for processing a cerium-doped gadolinium aluminum gallium garnet wafer, comprising the following steps: (1) Wafer cutting: cutting the crystal into wafers; (2) Laser drilling: drilling holes on the wafer using a laser; wherein the drilling speed is 5 mm / s to 100 mm / s; (3) Post-annealing treatment: The wafer after drilling is subjected to annealing treatment, wherein the annealing treatment conditions are: heating to 1100°C to 1400°C at a heating rate of 10°C / h to 40°C / h, keeping the temperature for 12h to 48h, and then cooling to room temperature at a cooling rate of 5°C / h to 30°C / h; (4) Optical processing: polishing the wafer after annealing.

2. The wafer processing method according to claim 1, wherein: In step (3), the annealing treatment conditions are: heating to 1200°C to 1400°C at a heating rate of 15°C / h to 30°C / h, keeping the temperature for 24h to 48h, and then cooling to room temperature at a cooling rate of 10°C / h to 20°C / h.

3. The wafer processing method according to claim 1, wherein: The diameter of the hole obtained after punching the wafer in step (2) is 0.5 mm to 10 mm, and the error of the diameter of the hole is less than or equal to 0.05 mm.

4. The wafer processing method according to claim 1, wherein: In step (1), the cutting speed is 0.1 mm / min to 1 mm / min, and the thickness of the wafer is 0.2 mm to 1 mm.

5. The wafer processing method according to claim 1, wherein: In step (4), the polishing steps include: coarse grinding, fine grinding, and chemical mechanical polishing.

6. The wafer processing method according to claim 5, wherein: The rough grinding comprises: rough grinding with diamond sand of W40 to W28; The fine grinding comprises: using W10-W7 corundum powder for fine grinding; The chemical mechanical polishing includes: grinding and polishing with a polishing liquid, wherein the rotation speed of the grinding and polishing is 5 rpm to 50 rpm and the pressure is 2 kPa to 20 kPa.

7. The wafer processing method according to claim 6, wherein: The polishing liquid includes CeO2, diamond micropowder, H3PO4, and deionized water, wherein the particle size of the diamond micropowder is 0.5 μm to 5 μm; based on the mass of the polishing liquid, the mass percentage of CeO2 is 1% to 10%, the mass percentage of the diamond micropowder is 10% to 20%, the mass percentage of H3PO4 is 1% to 5%, and the mass percentage of deionized water is 65% to 88%.

8. The wafer processing method according to claim 1, wherein: The processing yield rate of the wafer is greater than or equal to 70%.